Penggunaan Motion Capture Untuk Identifikasi Gerak Pada Budaya Kerja Tradisi Batik Tulis - Widyasari, Rachmi Kumala; Sachari, Agus; Sriwarno, ⁠Andar Bagus; Adhitama, Gregorius Prasetyo (Jurnal Sosioteknologi, 2024)
The knowledge of producing batik has been passed down from generation to generation. This research uses a motion capture device to document the batik-making activities using canting to yield accurate movement patterns of the batik artisans in digital form. The study aims to identify the hand movements of the batik artisans as they work with canting, which will serve as the basis for teaching the traditional batik-making process to beginners. This study starts with an ethnographic approach: observations and interviews conducted at several batik houses in Central Java, followed by ergonomic and human factors laboratory experiments. By analyzing the motion captures, we learn that a batik artisan makes a specific hand movement pattern known as Pola Layangan. Pola Layangan forms a cycle comprising four phases: the malam phase, the blowing phase, the drawing phase, and the finishing phase. The digital documentation of this hand movement pattern can serve as a reference for studying batik-making activities. It can also serve as a basis for teaching beginners the traditional batik-making process.